2021
DOI: 10.1071/an20605
|View full text |Cite
|
Sign up to set email alerts
|

Replacing maize with low tannin sorghum grains: lamb growth performance, microbial protein synthesis and enteric methane production

Abstract: Context Sorghum (Sorghum bicolor (L.) Moench) grain with low tannin content may be suitable as an alternative to maize (Zea mays L.) grain in ruminant diets in terms of input costs and drought tolerance, and effects on growth performance and mitigation of methane (CH4) emissions. Aims The study aimed to evaluate the effects of substitution of maize with sorghum grain at different rates on ruminal microbial protein synthesis, CH4 formation and liveweight gain in growing ruminants. Methods Twenty-five Santa In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Enhancements in PF values may also contribute to the CH 4 reduction observed by MNM CETAB [28]. Removing H+ from the rumen ecosystem is known to increase ruminal pH and to stimulate ruminal microbial activity; thus, when CH 4 decreases, H+ may be used for producing SCFAs to ensure optimal ATP yield for the microbial mass production [2].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancements in PF values may also contribute to the CH 4 reduction observed by MNM CETAB [28]. Removing H+ from the rumen ecosystem is known to increase ruminal pH and to stimulate ruminal microbial activity; thus, when CH 4 decreases, H+ may be used for producing SCFAs to ensure optimal ATP yield for the microbial mass production [2].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased lag time of CH 4 and CO 2 production with rations containing MOS was parallel with the result of increased GP. The secondary metabolites (e.g., tannins and phenolics) in MOS (Kholif and Olafadehan 2021 ) and variation in the chemical composition of the treatments (Soltan et al 2021 ) may be responsible for these effects. In their experiments, Kholif et al ( 2017 ) showed that chemical composition of incubated substrates affected in vitro production of CH 4 and CO 2 due to its effect on nutrient availability and microbial activity in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Karamshahi Amjazi et al ( 32 ) reported that the apparent digestibility of DM and CP was decreased with AM silage inclusion in a sheep diet. Moreover, total BW gain and ADG in AM-25 were numerically higher and this could provoke different rates of digestion, which might enhance the efficiency of energy utilization and consequently enhance growth rate ( 40 ). Analysis of feeding costs showed that inclusion of AM to diet led to a sensible reduction of the feed cost per kg BW gain (7.6 and 6.9% reduction with the inclusion of 25 and 50% AM and DM basis).…”
Section: Discussionmentioning
confidence: 99%